Disease transmission MSEIR model with individuals traveling between patches i and i+1 - Chaharborj, Sarkhosh Seddighi; Abu Bakar, Mohd Rizam; Ebadian, Alli (The Korean Society for Computational and Applied Mathematics, 2010)
In this article we want to formulate a disease transmission model, MSEIR model, for a population with individuals travelling between patches i and i + 1 and we derive an explicit formula for the basic repro- ductive number, R0, employing the spectral radius of the next generation operator. Also, in this article we show that a system of ordinary diﬀeren- tial equations for this model has a unique disease-free equilibrium and it is locally asymptotically stable if R0 < 1 and unstable if R0 > 1.